Histological comparison of DBBM and platelet rich fibrin for guided bone regeneration in a rabbit model - Andres Rezuc; Christian Saavedra; Rodrigo Maass; Cristian Poblete; Christian Nappe (Elsevier, 2020)
abstract: Purpose: To histologically evaluate the use of bovine derived deproteinized xenograft (DBBM), leukocyte and platelet rich fibrin (L-PRF) and the combination of both in Guided Bone Regeneration (GBR) performed in non-critical size defects in rabbit. Methods: A prospective experimental study was performed. Four bone defects in the tibiae of 12 rabbits were made and each of them was filled with DBBM, L-PRF, a combination of DBBM + L-PRF or was left to heal as control site. All defects were covered with a collagen membrane. Rabbits were randomly distributed in three groups and euthanatized at 3, 6 or 9 weeks. Samples were obtained and histologically analyzed to determine vital bone, connective tissue and remaining graft particles percentage. Analysis of variance, Kruskal Wallis and non-paired t-test where used to evaluate the significance of the results. Results: At 3 weeks of healing, DBBM showed significantly more vital bone percentage than L-PRF (p = 0,05) and DBBM + L-PRF showed significantly less connective tissue than control (p < 0,05). All other groups showed no statistical difference between them. At 6 weeks of healing, DBBM showed significantly more vital bone percentage than L-PRF (p < 0,05), DBBM + L-PRF (p < 0,05) and control (p < 0,05) and there wasn't any other significant difference regarding to connective tissue or remaining particle percentage between groups. At t 9 weeks healing period, there weren't any significant differences between groups. Conclusions: DBBM seems to enhance vital bone formation at early healing stages. The use of L-PRF alone or combined with DBBM, didn't show any histological improvement regarding to vital bone formation. The use of DBBM, alone or in conjunction with L-PRF showed a trend to reduce connective tissue percentage. The use of L-PRF combined with DBBM didn't affect the remaining particle percentage.